Model Matematika Optimasi Multi-Objektif Penurunan Beban Limbah Biochemical Oxygen Demand pada Instalasi Pengolahan Air Limbah - Shelly Sholatan Kamilah; Sunarsih Sunarsih; Titi Udjiani (Universitas Negeri Gorontalo, 2022)
The increase in community activities causes the amount of wastewater to increase. This wastewater comes from industrial production processes and from the community activities which are domestic wastewater. Domestic wastewater must be treated before being discharged to water sources because it contains pathogenic organisms. The place for treating domestic wastewater is Wastewater Treatment Plant (WWTP). The main purpose of WWTP is to degrade the Biochemical Oxygen Demand (BOD) and pathogenic organisms. This study develops a multi-objective optimization mathematical model for reducing the BOD load in the WWTP. This optimization model has three objective functions, namely maximizing the BOD load that is treated in the pond minimizing the difference between the BOD reduction efficiency value in the WWTP with the reference efficiency value and minimizing the power used by the aerator. The simulation results show that the maximum BOD load that can be treated in facultative ponds I and II is 1,589.688 Kg/day while for facultative ponds III and IV is 1,727.158 Kg/day. The efficiency value of reducing BOD load is influenced by the residence time variable, where the efficiency value of reducing the BOD load for facultative ponds I and II by 54% while for facultative ponds III and IV by 57%. The power used by the aerator is influenced by the treated BOD load variable, the aerator power in facultative ponds I and II is 49.67775 Kwh while in facultative ponds III and IV it is 53.97369 Kwh.